2012
DOI: 10.1016/j.bbamcr.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

A role of DNA-dependent protein kinase for the activation of AMP-activated protein kinase in response to glucose deprivation

Abstract: The catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) plays an essential role in double-strand break repair by initially recognizing and binding to DNA breaks. Here, we show that DNA-PKcs interacts with the regulatory γ1 subunit of AMP-activated protein kinase (AMPK), a heterotrimeric enzyme that has been proposed to function as a "fuel gauge" to monitor changes in the energy status of cells and is controlled by the upstream kinases LKB1 and Ca²⁺/calmodulin-dependent kinase kinase (CaMKK). In co-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…Supporting our findings, the association between DNA-PKcs and AMPK has been identified by two previous studies. Amatya and coworkers have demonstrated an interaction between DNA-PKcs and AMPKg using yeast 2-hybrid method and co-immunoprecipitation from mammalian cells (Amatya, Kim et al, 2012), while Lu and coworkers have verified this interaction in mammalian cells by co-immunoprecipitation and immunocytochemistry (Lu, Tang et al, 2016). In line with our data, these studies have also identified DNA-PKcs as a positive regulator of AMPK activity, however, without addressing the underlying mechanism.…”
Section: Discussionsupporting
confidence: 75%
“…Supporting our findings, the association between DNA-PKcs and AMPK has been identified by two previous studies. Amatya and coworkers have demonstrated an interaction between DNA-PKcs and AMPKg using yeast 2-hybrid method and co-immunoprecipitation from mammalian cells (Amatya, Kim et al, 2012), while Lu and coworkers have verified this interaction in mammalian cells by co-immunoprecipitation and immunocytochemistry (Lu, Tang et al, 2016). In line with our data, these studies have also identified DNA-PKcs as a positive regulator of AMPK activity, however, without addressing the underlying mechanism.…”
Section: Discussionsupporting
confidence: 75%
“…response to glucose-free conditions (59). However, although CRY1 is a substrate for AMPK, this is unlikely to be the mechanism in this case, because DNA-PK activates AMPK (rather than inhibiting its activity) and because the Ser-588 site on CRY1 is part of an SQ motif, which is not predicted to be a phosphorylation site for AMPK.…”
Section: Discussionmentioning
confidence: 97%
“…AMP-activated protein kinase (AMPK) is an energy sensor that acts as a metabolic master switch influencing numerous processes [81]. DNA-PKcs interacts with the regulatory λ1 subunit of AMPK, and glucose-deprivation stimulated phosphorylation of AMPK is decreased in DNA-PKcs deficient cells [82]. Further, DNA-PKcs inhibition or depletion resulted in reduced AMPK phosphorylation and activation in response to glucose deprivation, suggesting that DNA-PKcs positively regulates AMPK phosphorylation and activation in glucose-deprived conditions.…”
Section: Dna-pk: Cellular Consequencesmentioning
confidence: 99%